Development and validation of hydraulic driven electronic penetrometer for georeferenced point collection - Camila W. L. Parize; Thiago X. da Silva; Leonardo L. Kmiecik; Guilherme L. Parize; Yasser A. Oiole; Samir P. Jasper (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Soil penetration resistance (SPR) is used as an indicator of compaction, as it is related to important soil and plant attributes and is an easily obtainable measure. Its determination with the use of the penetrometer guides to the best soil management strategies, thus favoring crop development. The objective of this study was to develop and validate the georeferenced hydraulic driven electronic penetrometer, making it easier to obtain SPR. For this, 36 SPR readings from 0 to 0.60 m depth were performed with the manual and hydraulic penetrometers in two areas. The SPR results were analyzed by establishing the confidence intervals by the t-test (p ≤ 0.10) at each 0.05 m depth and the georeferencing was analyzed through the root mean square error (RMSE). It was found that both penetrometers showed similarity in SPR measurement and in the georeferencing of the points.